Manufacture of UAV Skywalker 1900 Flying Vehicles Made of Composites - Ferry Setiawan; Muhammad Fauzaan Firmansyah; Dhimas Wicaksono; Ikbal Rizki Putra (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2022)
The purpose of this research is to make a flying vehicle with the SKYWALKER 1900 UAV model for mapping missions with fiber glass reinforced composite materials on the wings and carbon fiber on the fuselage and tail. With composite materials, it is hoped that the structure of the UAV SKYWALKER 1900 will be stronger than previous materials using styrofoam. The method for making flying vehicles in this study uses 3D printing, to print UAV parts such as wings, fuselag and tail. then molding for components is made, and the final stage is manufacturing parts with composites using glass fiber and carbon fiber reinforcement using the vacuum bagging method. the analysis of weight deviation on the fuselag has a value of 70% and the weight deviation on the wings is 52%, the size deviation on the fuselag and wings weight occurs due to the putty process during finishing. the results of the aerodynamic analysis on the fuselag using solid work software, the UAV flight limit is 20 m/s to get the best flight results when flying